2015
DOI: 10.1016/j.ajic.2014.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Hospital unit safety climate: Relationship with nurses' adherence to recommended use of facial protective equipment

Abstract: Unit-level safety climate measures varied significantly between units. Strategies to improve unit-level communication regarding safety should assist in improving adherence to FPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
1
19
0
5
Order By: Relevance
“…The researchers found that organizational characteristics such as staffing and teamwork within units were correlated with overall standard precaution adherence. In addition, Rozenbojm, Nichol, Spielmann, and Holness () performed a secondary data analysis investigating hospital unit safety climate and its relationship to nurses’ adherence to using facial protective equipment. The analysis found that safety climate varies significantly between units and that nurses’ individual tenure and unit‐level communication were significant predictors of the adherence to use of facial protective equipment.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers found that organizational characteristics such as staffing and teamwork within units were correlated with overall standard precaution adherence. In addition, Rozenbojm, Nichol, Spielmann, and Holness () performed a secondary data analysis investigating hospital unit safety climate and its relationship to nurses’ adherence to using facial protective equipment. The analysis found that safety climate varies significantly between units and that nurses’ individual tenure and unit‐level communication were significant predictors of the adherence to use of facial protective equipment.…”
Section: Introductionmentioning
confidence: 99%
“…This might be explained by their significantly higher levels of satisfactory knowledge at the preintervention phase. Similar variations in the nurses' knowledge and practice of ICMs was revealed in a study in Canada, and this was not only among hospitals but also among the units of the same hospital according to the nurses' perception of organizational support for safety [19]. The multivariate analysis also identified nurse's age as a significant independent negative predictor of the knowledge score, which might be explained by the higher enthusiasm, more eagerness to learn, and higher ability to assimilate new information among the younger age nurses.…”
Section: Discussionmentioning
confidence: 82%
“…To examine the correlation between radiation safety education and nurses' compliance with safety procedures, age (Gershon et al, 2000), educational level (Kim et al, 2016), annual income (Jeong, Han, Park, & Ryu, 2016), marital status (Vidovich, Khan, Xie, & Shroff, 2015), years of experience in nursing (Kim et al, 2016), duration of employment involving radiation (Yoon & Yoon, 2014), geographical location (Gershon et al, 2000;Hong & Shin, 2014), number of hospital beds (Slechta & Reagan, 2008) and hospital safety climate (Rozenbojm, Nichol, Spielmann, & Holness, 2015) were considered as potentially confounding variables. The measurement for each variable is presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%